About cumulative idle time model of the message switching system - Minkevicius, S. (CUBO, A Mathematical Journal, 2013)
The purpose of this research in the queueing theory is the theorem about the law of the iterated logarithm in multiphase queueing systems and its application to the mathematical model of the message switching system. First the law of the iterated logarithm is proved for the cumulative idle time of a customer. Finally we present an application of the proved theorem for the model of the message switching system.